Assessment of Microbial Safety of Cheese and Sausage Products Sold in the Supermarkets of the City of Yerevan - Pipoyan, D. A.; Beglaryan, M. R.; Stepanyan, S. A.; Amirjanyan, A. H. (ՀԱԱՀ հիմնադրամ)
The aim of this study is to assess the microbial safety of sliced sausage and cheese products sold in Yerevan. Microbiological indices defined by the Eurasian Economic Union (EAEU) technical regulations were studied in the products sampled from Nor Zovk, Yerevan City and SAS supermarkets. The results indicated that before being sliced in supermarkets, the studied food products met the established safety requirements. However, microbiological contamination was detected in 71.4 % of sliced sausage product samples and in 33.3 % of sliced cheese samples. Therefore, it can be concluded that cutting these food products at sale points can contribute to their microbial contamination, making these foods unsafe for consumption.
Keywords: Food Science and Technology